Implementasi Algoritma SHA-256 Pada Aplikasi Duplicate Document Scanner - Sopiana Nainggolan (STMIK Budi Darma, 2022)
On a computer, if we duplicate a file, the duplicated file is no different from the first file and this can be done in a fairly short time. In this case, what will be duplicated is a word document file with docx extension. SHA (Secure hash Algorithm) is a hash algorithm that is relatively new. The selection of the SHA-256 algorithm is inseparable from several previous studies that have examined the performance of this algorithm. The SHA-256 algorithm is able to detect changes that occur in digital images even though the changes that occur are only 1 pixel, the small differences that occur in the image produce a very significant difference from the hash value with an accuracy level of up to 100%. SHA - 256 produces a message digest with 256 bits in length. SHA - 256 is classified as safe because it is designed in such a way that it is not possible to get messages related to the same message digest.